Utilization Monument Struggle of 45 Limbangan Kendal As Source Learning History in Students Class XI IPS SMA Negeri 1 Limbangan Kendal - Mahmudah, Sofnia Nurul; Saraswati, Ufi (Indonesian Journal of History Education, 2016)
The purposes of this study were: 1. to find out how the teacher uses existing history learning sources in class XI IPS, 2. To find out how the Monument Perjuangan 45 Limbangan can be used as a learning source of history of the students of XI IPS, 3. To find out the understanding of XI IPS students using Monument The Struggle of 45 Limbangan as a source of learning in SMA Negeri 1 Limbangan Kendal. This research was a qualitative study case. The source of the data of this study was SMA Negeri 1 Limbangan. The subjects of this study were class XI IPS students at SMA 1 Limbangan and the historical relic of Monuments, The Struggle of 45 Limbangan. The target/focus of this study was the learning resources. Observation, interviews, and documentation carried out data collection techniques. The history teacher of SMA Negeri 1 Limbangan utilized learning sources from the surrounding environment as the learning sources companion, besides books, modules, and internet sources, by linking relics with the learning material and using Monuments Perjuangan 45 Limbangan as the learning source by linking it with the relevant learning material. Teachers at SMA Negeri 1 Limbangan can use Monument Perjuangan 45 Limbangan to increase students' understanding because students can see their learning resources directly.